Learning Styles and Attitude toward Achievement among English Second Language Students - Nur Naenah, Nuning (LPPM Universitas Advent Indonesia, 2022)
English as a Second Language (ESL) is a mandatory class for international students when they come to study abroad, particularly those who come from unspoken English country. This study aims to identify the correlation between learning styles and attitude of AIIAS ESL and their academic achievement. The respondents of this study were thirty-two AIIAS ESL students. Using Pearson r correlation, this study showed that none correlated with the respondents' achievement among the six types of Reid’s learning style (the highest r-value is ≤ 0, 209 while the lowest is ≥ - 0, 263). In contrast, the attitude and achievement in this study showed a positive correlation. Among the three aspects of attitude, the emotion and achievement are significantly correlated (r value: 0.487; p value: 0.005). Meanwhile, the cognitive and attitude is significantly correlated with the r value: 0,427 (p value: =0.05). The weakest correlation with their attitude is behaviour where the r value is only 0.201 (p value: 0.269). Thus, students should be aware of their own learning styles to learn a new language better. In terms of attitude, students should maintain a positive attitude toward learning English to achieve good grades in their learning process